Asymptomatic Urolithiasis Complicated by Nephrocutaneous Fistula - Hamard, Marion; Amzalag, Gaël; Becker, Christoph D; Poletti, Pierre-Alexandre
Asymptomatic spontaneous nephrocutaneous fistula is a rare and severe complication of chronic urolithiasis. We report a case of 56-year-old woman with a nephrocutaneous fistula (NFC) which developed from a superinfected urinoma following calyceal rupture due to an obstructing calculus in the left ureter. The patient was clinically asymptomatic and came to the emergency department for a painless left flank fluctuating mass. This urinoma was superinfected, with a delayed development of renal abscesses and perirenal phlegmon found on contrast-enhanced uro-computed tomography (CT), responsible for left renal vein thrombophlebitis and left psoas abscess. Thereafter, a 99 mTc dimercaptosuccinic acid (DMSA) scintigraphy revealed a nonfunctional left kidney, leading to the decision of left nephrectomy. Chronic urolithiasis complications are rare and only few cases are reported in medical literature. A systematic medical approach helped selecting the best imaging modality to help diagnosis and treatment. Indeed, uro-CT scan and renal scintigraphy with 99 mTc-DMSA are the most sensitive imaging modalities to investigate morphological and functional urinary tract consequences of NFC, secondary to chronic urolithiasis.